Phenetic relationships among Argentine species of Alstroemeriaceae - Sanso, A.M. (1997)
Cluster analysis and ordination by principal component analysis (PCA) were used to study phenetic relationships among the Argentine species of Alstroemeriaceae and to point out the characters that contribute to the differentiation between Alstroemeria L. and Bomarea Mirb. A total of 123 specimens (analysis 1) and 15 taxa (analysis 2) were examined and 46 morphological characters were used: 17 quantitative and 29 qualitative ones. The results point out the clear phenetic distinction between Alstroemeria and Bomarea species and also among species within both genera. A dendrogram produced by UPGMA cluster analysis on standardized characters and the PCA analysis show the differentiation of Bomarea species into two groups: B1 includes Bomarea stans Kränzl., B. boliviensis Baker (subgen. Sphaerine) and B. edulis (Tuss.) Herb, (subgen. Bomarea) respectively, and B2 with B. macrocephala Pax. (subgen. Wichuraea). For the Alstroemeria species, four groups are recognized: A1 is formed by Alstroemeria apertiflora Baker, A. bakeri Pax and A. isabellana Herb.; A2 comprises two subgroups, A2a: A. psittacina Lehm., A. presliana Herb, and A. aurea Graham and A2b with A. pygmaea Herb, and A. patagonica Phil, (with A. patagonica Phil. f. biflora Ravenna). A. pseudospathulata Ehr. Bayer (A3) and A. andina Phil, subsp. venustula (Phil.) Ehr. Bayer (A4) have isolated positions.